Frequencies and severity of injection-site lesions in muscles from rounds of cow carcasses. Issue 1 (25th September 2018) - Pfeiffer, Morgan M; Mafi, Gretchen G; Ramanathan, Ranjith; Neilson, Taylor M; VanOverbeke, Deborah L
Abstract: The frequency and severity of injection-site lesions in the outside round muscles of both beef and dairy cattle were evaluated through a series of audits. Audits were conducted in 2017 on 1, 300 rounds from dairy and beef cows from seven locations throughout the United States. Outside round muscles were butterfly cut into 1.25-cm slices and, if present, lesions were counted, measured, and categorized. Rounds from beef (7%) and dairy cattle (15%) had at least one injection-site lesion present. The most common location of injection-site lesions was quadrant 2 and 3, which contained both the biceps femoris and semitendinosus muscles. Injection-site lesions were more frequent ( P < 0.05) in the biceps femoris for both beef and dairy rounds. Clear lesions accounted for 57% of injection-sites in both beef and dairy rounds, whereas metallic lesions made up 23% of the total in beef and 25% in dairy. Overall, there was a dramatic decline in the frequency ( P < 0.05) of injection-site lesions since the 1998 (24 and 45 percentage units greater in beef and dairy rounds, respectively) and 2000 audits (13 and 20 percentage units greater in beef and dairy rounds, respectively). Educational programs, such as Beef Quality Assurance (BQA) and requirements for BQA training, have resulted in substantial improvements in beef management practices for both the beef and dairy industries.